Should Anne worry about private intellectual property projects? The Creative Commons case - Selep, Ján (2011)
Creative Commons (CC) organization released in 2003 six licenses, which take part of the copyright protection and let other parts fall in the public domain. Consequently, they lower the price of works for future works (inputs) and as an outcome increase creativity and number of works created. On the other hand, CC licenses can serve also as a substitutes to the pure copyright. This thesis examine the impact by analysing United States copyright registration and CC linkback data. The results show insignificance of CC licenses impact on pure copyright licenses. Based on the results I found weak evidence for complementary relationship between the two. Finally, I show that there is no difference between the types of CC licenses as an determinants of number of pure copyright licenses.